PEMANFAATAN BUAH Sonneratia alba MENJADI SIRUP MANGROVE DI SEKITAR KAWASAN MANGROVE LUNG MANE NAGAN RAYA ACEH - Wintah Wintah; Kiswanto Kiswanto; Nurdin Nurdin (Universitas Teuku Umar, 2022)
Lung Mane coastal area has magrove forest which reaches an area of 40 ha. The dominant mangrove tree species that grow are Rhizophora sp and Sonneratia sp. Mangrove plants that have a high enough quantity of fruit are Sonneratia alba because at times of unseason, trees can still produce approximately 2 kg / day. Sonneratia alba fruit can be processed to be used as a beverage product in the form of syrup. Sonneratia alba fruit syrup is one of the processed products of mangrove fruit that can increase the economic and ecological value of mangrove forests and can increase the income of people living around mangrove forests, so that by utilizing mangrove fruit into various processed foods and drinks the community is helped economically and indirectly participates in maintaining the sustainability of mangrove forests around them.